Breaking Corn Yield Barriers: A Cropping Systems Approach - G. R. Balboa; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2015)
A corn research trial was conducted at Scandia, KS, during the 2014 growing season. The objective was to study the contribution of different farming systems in developing efficient and high-yielding corn production systems. The experiment had five treatments: farmer practices, comprehensive fertilization, production intensity, ecological intensification, and advanced plus. Farmer practice was the lowest-yielding treatment, and ecological intensification and advanced plus treatment presented similar yields.
Keywords: corn; high-yielding cropping systems; yield gaps